Hierarchical peroxiredoxin assembly through orthogonal pH-response and electrostatic interactions - Anaya-Plaza, Eduardo; Özdemir, Zulal; Wimmer, Zdenek; Kostiainen, Mauri A (Journal of materials chemistry. B, 2023)
Morpheeins are proteins that adapt their morphology and function to the environment. Therefore, their use in nanotechnology opens up the bottom-up preparation of anisotropic metamaterials, based on the sequential use of different stimuli. A prominent member of this family of proteins is peroxiredoxins (Prx), with dual peroxidase and chaperone function, depending on the pH of the media. At high pH, they show a toroidal morphology that turns into tubular stacks upon acidification. While the toroidal conformers have been explored as building blocks to yield 1D and 2D structures, the obtention of higher ordered materials remain unexplored. In this research, the morpheein behaviour of Prx is exploited to yield columnar aggregates, that are subsequently self-assembled into 3D anisotropic bundles. This is achieved by electrostatic recognition between the negatively charged protein rim and a positively charged porphyrin acting as molecular glue. The subsequent and orthogonal input lead to the alignment of the monodimensional stacks side-by-side, leading to the precise assembly of this anisotropic materials.
Keywords: Peroxiredoxins; peroxiredoxiny; Nanotechnology; nanotechnologie; koncentrace vodíkových iontů; Hydrogen-Ion Concentration; peroxidasa; Static Electricity; Peroxidase; statická elektřina